Species richness and functional groups of angiosperms from the Paraná River Delta region (Argentina) - Madanes, Nora (2015)
We provide a checklist of angiosperms collected in the Paraná River Delta Region during the 1990s and early 2000s. Plants were taxonomically identified and classified according to their origin (native/endemic and exotic) and functional group based on their distribution, biological type, morpho-ecology, photosynthetic type and life cycle. A total of 79 families and 375 species were recorded, of which 87.5% were native (46.93% of subtropical-temperate distribution) and 12.5% were exotic (62.72% of temperate distribution). The herbaceous broadleaf and graminoid vegetation predominated in native (76.65%) and exotic (82.35%) species groups. There were only equisetoid herbaceous plants in native species group. Rooted emergent plants and the C3 functional group predominated among native (88.69% and 80.62%, respectively) and exotic (100% in both cases) species groups. Most of the native plants (85.23%) were perennials, while annuals and perennials were equally represented among the exotic species.